Donna, che fosti tra le donne un Sole»: sui tentativi poetici giovanili di Paolo Paruta (metà XVI sec.) - Giani, Marco (Italianistica Debreceniensis, 2017)
During the mid-1560s, Paolo Paruta (1540-1598), future Ambassador of the Republic of Venice in Rome (1591-1595) and author of the three books of Perfettione della Vita Politica (Venice, 1579) wrote some poems: the canzone Donna, che fosti tra le donne un Sole, and three somnets. The former was then published in Dionigi Atanagi’s Rime di diversi nobilissimi et eccellentissimi autori, in morte della Signora Irene delle Signore di Spilimbergo (Venice, 1561), the latters were insert in Diomede Borghesi’s anthology for Cinzia Braccioduro Garzadori (then published in Padua, 1567, without Paruta’s somnets).Writing those juvenile poems and making them circulate among the Venetian literary circles (such as Domenico Venier’s), Paruta was looking not only for artistic approval, but also for social visibility: the canzone and the somnets were part of his wider strategy for social climbing inside Venetian patrician ruling class.